8. COMPARISON OF NATURAL CYCLES VERSUS HORMONE REPLACEMENT TREATMENT FOR 2398 FROZEN–THAWED EMBRYO TRANSFER CYCLES FOR PREIMPLANTATION GENETIC TESTING PATIENTS. (August 2019) - Fu, Y.; Shen, X.; Zhou, C.
Abstract : Introduction: Multiple studies have been performed to evaluate the efficiencies of various endometrial preparation protocols. However, to date, the most appropriate method of endometrial preparation for frozen-thawed embryo transfer (FET) remains debated. To our knowledge, there are no studies comparing FET cycle endometrial preparation protocol for PGT patients, and this study is the first study to compare FET cycle endometrial preparation protocols for PGT patients. Material & methods: This retrospective analysis included 2398 FET cycles for 1497 preimplantation genetic testing (PGT) patients with regular menstrual cycles who underwent frozen-thawed single blastocyst transfer from January 2014 to December 2017. The patients were divided into two groups according to the method of endometrial preparation for FET: 586 cycles were natural cycles(NC), and 1812 cycles were hormone replacement treatment (HRT). Reproduction-related clinical outcomes of the two groups were compared. Results: The NC group showed a higher clinical pregnancy rate (54.78% vs 51.66%, P=0.188) and live birth rate (45.22% vs 43.21%, P=0.394) than did the HRT group, but these differences were not statistically significant. Moreover, endometrial thickness was significantly greater in the NC group (9.91±2.05 mm vs 8.95±1.53 mm, P<0.001). Furthermore, the ectopic pregnancy rate was significantly higher in the HRT group (0% vs 1.5%, P=0.028). The cesarean section rate (64.75% vs 52.45%, P<0.001) and pregnancy complication rate (21.47% vs 15.58%, P=0.023) were also significantly higher in the HRT group. Conclusion: Our study shows a trend towards higher pregnancy rate and live birth rate for NC compared to HRT. Large randomized controlled trials are warranted to confirm this trend. Additionally, NC is safer than HRT, avoiding ectopic pregnancy and adverse obstetric outcomes.